Exploring the Applicability of Green Lean Tools and Methods in Progressive Die Stamping - Dawid BOGDANOWICZ; Maria ROSIENKIEWICZ (Communications of International Proceedings, 2025)
The increasing pressure on manufacturing industries to adopt sustainable practices requires the integration of environmental management with traditional efficiency-oriented systems. While Lean manufacturing aims to eliminate non-value-adding activities, it does not explicitly address environmental impacts such as emissions, energy consumption, or resource use. This gap has led to the emergence of the Green Lean concept, which combines Lean and environmental management principles to achieve sustainable manufacturing outcomes. Despite the increasing body of literature on Green Lean, research remains largely conceptual, with limited empirical validation – particularly in energy-intensive sectors like metal forming and progressive die stamping. Addressing this void, the present study aims to identify and analyze Lean tools and methods adapted for sustainability and to evaluate their applicability to progressive die stamping. A literature-based analytical methodology was employed, consisting of four main steps: (1) identifying classical Lean tools; (2) selecting sustainability-oriented adaptations such as Sus-TPM, Green-SMED, and Eco-Design; (3) assessing their potential for implementation in progressive die stamping; and (4) synthesizing the findings into a framework linking Lean methods with sustainability outcomes. The study demonstrates that tools such as Sustainable VSM, Green-SMED, and Sustainable TPM can effectively enhance energy efficiency, reduce material waste, and minimize emissions in stamping operations. The results provide a structured foundation for applying Green Lean principles in metal forming industries and serve as a basis for future empirical research and industrial implementation.
Keywords: Lean manufacturing; Green Lean; Sustainable Manufacturing; Progressive die stamping